2014
DOI: 10.1016/j.jcat.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies of the adsorption geometry and reaction pathways of furfural over FeNi bimetallic model surfaces and supported catalysts

Abstract: Controlling the activity and selectivity of hydrodeoxygenation (HDO) of biomassderivatives is critical for the utilization of biomass as renewable sources for chemicals and fuels. Furfural, produced by the hydrolysis and dehydration of xylose from hemicellulose, is a promising biomass-derivative to produce important biofuels like 2-methylfuran. Using a combination of density functional theory (DFT) calculations and surface science measurements on Fe/Ni(111) model surfaces, our results indicate that furfural bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 35 publications
4
92
0
Order By: Relevance
“…Several studies have argued the high selectivities of the studied bimetallic catalysts is due to the oxophilicity of the secondary metal [9,[12][13][14]. For example, Resasco and coworkers [9] observed that NiFe catalysts showed superior selectivity compared to Ni for the reaction of furfural to methyl furan.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have argued the high selectivities of the studied bimetallic catalysts is due to the oxophilicity of the secondary metal [9,[12][13][14]. For example, Resasco and coworkers [9] observed that NiFe catalysts showed superior selectivity compared to Ni for the reaction of furfural to methyl furan.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of furfural reaction on hydrogen pre-dosed Fe/Ni(111) surfaces has been published previously [29]. The results of furfural on clean Ni(111) and ML Fe/Ni(111) surfaces are presented here to draw a comparison with C 2 oxygenates, glycolaldehyde and acetaldehyde.…”
Section: Tpd Experiments Of Furfural On Fe/ni(111) Surfacesmentioning
confidence: 97%
“…After deposition, the composition of the ML Fe/Ni(111) surface was estimated using the AES method described previously [28]. The relative Auger intensity ratio (I Fe /I Ni ) for the ML Fe/Ni(111) surface is around 0.15 [29].…”
Section: Surface Science Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of bimetals in catalytic performance has been attempted by adding a metal to a Ni, Cu, or noble metal base [25][26][27]. In particular, the active site, which plays an important role in the catalytic reaction, has been investigated theoretically and experimentally by controlling the atomic ratio and modifying the surface [28][29][30].…”
Section: Introductionmentioning
confidence: 99%